Characteristics of serrated chip formation in high-speed machining of metallic materials. Issue 5 (September 2016) - Yang, Qibiao; Wu, Yin; Liu, Dun; Chen, Lie; Lou, Deyuan; Zhai, Zhongsheng; Liu, Zhanqiang
Abstract A study on the mechanism of serrated chip formation has been carried out. Characterization of serrated chip is performed using geometrical methods, including degree and frequency of segmentation, base angle, and bottom edge. Mechanical characterization such as micro-hardness is also adopted. Experiments of high-speed machining on three metallic materials including Ti6Al4V, hardened 1045 steel, and Al7050 are performed. The chips of the three metallic materials under different cutting speeds are collected during high-speed machining. After polishing, the serrated chip is observed under a digital microscope. The results show that the degree and frequency of segmentation increase with the cutting speed. Al7050 is most sensitive to these parameters. The hardened 1045 steel is similar to the titanium alloy Ti6Al4V. Both the base angle and the vertex angle decrease with the cutting speed. The specific geometry of serrated chip unit under certain cutting speed can be determined by using the geometric characterization parameters. The micro-hardness of the four vertices increases with the increase of cutting speed.